Inverse Gaussian Model to Describe the Distribution of Age Specific Fertility Rates of Nepal - Gaire, Arjun Kumar; Aryal, Roshan (Journal of Institute of Science and Technology, 2015)
This paper attempts to formulate Inverse Gaussian probability model to describe the distribution of the age specific fertility rates among Nepalese mothers. The average age of child bearing has been found to be 26.12 years whereas child bearing starts at the age of 15.82 years. Estimated total fertility rate (TFR) has been found to be 2.60 against the observed value of 2.6 per woman. The coefficient of determination and chi-square values suggest that the model found to be good fit to the Nepal Demographic and Health Surveys data. Findings may help researchers and policy makers for applying the model in order to obtain the descriptive statistics for policy interventions. Journal of Institute of Science and Technology, 2015, 20(2): 80-83